PENGARUH KEPEMIMPINAN KEPALA SEKOLAH WANITA TERHADAP KINERJA GURU: STUDI KASUS DI SEKOLAH DASAR ISLAM DI INDONESIA - Wahyudi, Wahyudi; Nasikhin, Nasikhin; Novitasari, Mia (Fitrah, 2023)
This study aims to analyze the influence of female school principal leadership on teacher performance. Using quantitative research, this study shows that women's leadership has a significant influence on teacher performance, with 83.3% being in the high category. The results confirm the strong role of female school principals in improving the quality of teacher performance. Every one-point increase in the leadership pattern of female school principals has an impact on improving teacher performance by 1,255 points. In addition, the significant test shows a significant effect between the two with T count (3,731) exceeding T table (2,051), rejecting the null hypothesis (H0) and accepting the alternative hypothesis (Ha). Nonetheless, only about 33.2% of the variation in teacher performance can be explained by the leadership of female school principals, while the remainder, around 66.8%, is influenced by other factors that need further investigation. This study contributes to supporting women to achieve the highest leadership positions in schools. This not only creates greater gender equality in education, but can also enrich diversity in decision-making and perspectives that may be overlooked in school leadership.